Dosimetric Impact of a Tumor Treating Fields Device for Glioblastoma Patients Undergoing Simultaneous Radiation Therapy - Li, Taoran; Shukla, Gaurav; Peng, Cheng; Lockamy, Virginia; Liu, Haisong; Shi, Wenyin (Frontiers in Oncology, 2018)
PURPOSE: A recent randomized phase III clinical trial in patients with glioblastoma demonstrated the efficacy of tumor-treating-fields (TTFields), in which alternating electric fields are applied via transducer arrays to a patient’s scalp. This treatment, when added to standard of care therapy, was shown to increase overall survival from 16 months to 20.9 months. These results have generated significant interest in incorporating the use of TTFields during post-operative concurrent chemoradiation. However, the dosimetric impact of high density electrodes on the scalp, within the radiation field, is unknown. METHODS: The dosimetric impact of TTFields electrodes in the radiation field was quantified in two ways: (1) dose calculated in a treatment planning system, and (2) physical measurements of surface and deep doses. In the dose calculation comparison, a volumetric-modulated-arc-therapy (VMAT) radiation plan was developed on a CT scan without electrodes, and then re-calculated with electrodes. For physical measurements, the surface dose underneath TTFields electrodes were measured using a parallel plate ionization chamber and compared to measurements without electrodes for various incident beam angles and for twelve VMAT arc deliveries. Deep dose measurements were conducted for 5 VMAT plans using Scandidos Delta4 diode array: measured doses on two orthogonal diode arrays were compared. RESULTS: In the treatment planning system, the presence of the TTFields device caused mean reduction of PTV dose of 0.5-1%, and a mean increase in scalp dose of 0.5-1 Gy. Physical measurement showed increases of surface dose directly underneath by 30% to 110% for open fields with varying beam angles, and by 70% to 160% for VMAT deliveries. Deep dose measurement by diode array showed dose decrease of 1-2% in most areas shadowed by the electrodes (max decrease 2.54%). CONCLUSION: The skin dose in patients being treating with cranial irradiation for glioblastoma may increase substantially (130%-260%) with the addition of concurrent TTFields electrodes on the scalp. However, the impact of dose attenuation by the electrodes on deep dose during VMAT treatment is of much smaller, but measureable, magnitude (1-2%). Clinical trials exploring concurrent TTFields with cranial irradiation for glioblastoma may utilize scalp-sparing techniques to mitigate any potential increase in skin toxicity.